Social Mapping of Cultural Production : Strategies in dealing with the decline in tourism due to the Covid19 pandemic in Penglipuran Village, Bali - I Wayan Gede Lamopia; Riza Wulandari; Isma Illia Shara Yunianti (Universitas Muhammadiyah Sidoarjo, 2021)
Panglipuran village is a reflection of balinese in the field of tourism. In anticipating the decrease of visitors in Panglipuran due to the covid19 pandemic, it is necessary to conduct a scientific study, namely social mapping of cultural production. The study aims to ease the people in Panglipuran village to explore the potential of the village to recover economic condition due to the decrease of tourists. Based on the bordieu paradigm and field observation, there are four potential assets in dealing with the crisis, namely symbolic, cultural, economic, and social assets.